Pengaruh Penggunaan Petunjuk Praktikum IPA Berbasis Learning Cycle Terhadap Practical Skills Siswa Kelas IV Sekolah Dasar - Chan, Faizal; Budiono, Hendra (Jurnal PGSD, 2020)
This study aims to determine whether there is an effect of the use of learning cycle-based science practicum instructions on the practical skills of fourth grade students of SDN 131 / IV in Jambi City. This research was carried out at SDN 131 / IV Jambi City with the research subjects were 13 grade students. This research is a quasi-experimental one group pretest posttest design. The results showed that the significance value of the pretest and posttest was -7.610 small from the alpha value of 0.05 (-7.610 <0.05) which means that there is a significant influence between the use of learning cycle-based science practicum instructions on the practical skills of grade IV elementary schools. It can be concluded that there is a significant influence between the use of learning cycle-based science practicum instructions on the practical skills of class IV SDN 131 / IV Jambi City.